Santa Rosa Intercity Bus Terminal revitalizing transport experience at the Lion City of South Luzon - Ynion, James Anjolo C. (College of Architecture, University of the Philippines Diliman, 2019)
The Santa Rosa Intercity Bus terminal is the architectural intervention that serves as a new competitor to the current intercity terminals of the vicinity. The facility houses the bus terminal, leasable spaces, office spaces, and a depot for the transport buses. This project aims to be the central transport hub for the visitors, students and working class alike going in and out of the city on almost a daily basis, all with one goal to make everyone's transport experience comfortable, efficient and different among the rest.